Pay-Per-View Sales In Decline: Evaluating Why Boxing Ppvs Are No Longer Selling (Eurasian Journal of Humanities and Social Sciences, 2024)
Pay-per-view (PPV) has been a major source of revenue for premier boxing events for decades. However, PPV buy rates have steeply declined in recent years. This article analyzes the reasons behind the falling sales of boxing PPVs. Through an examination of industry data, media coverage, and academic business and media scholarship, it assesses various factors potentially contributing to reduced demand. The literature review summarizes discourse around rising prices, illegal streaming, audience fragmentation in the digital age, declining match quality and star power, and failure to cultivate new fanbases. The analysis suggests that while no single reason fully accounts for the trend, the interplay of increased accessibility of unauthorized broadcasts, unappealing bouts failing to create drama and meaning for audiences, and the sport’s inability to expand beyond its aging loyalists significantly explain boxing’s struggles to thrive as a PPV product compared to its peak. The article concludes by reflecting on the precarious state of the PPV boxing model and options stakeholders have to revive interest